2022
DOI: 10.2147/rmhp.s367730
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Health Seeking Behavior of Patients with Chronic Disease at Public Hospitals in Jimma Zone, South West Ethiopia

Abstract: Background: COVID-19 is a global pandemic with unprecedented medical, economic and social consequences affecting nations across the world. This epidemic arises while chronic diseases are continued to be a public health concern. Though evidence is generated on its impact on the health care system, little is known about the Impact of COVID −19 on the care-seeking behavior of chronic patients. Objective: To assess the Impact of COVID-19 on healthcare-seeking behavior of patients with chronic diseases attending fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of follow-up care and poor healthcare utilization in sub-Saharan Africa were the most frequently reported challenges reported by ten studies included in this systematic review [10,11, 23,24,25,26,27,28,29,30,31]. Some of the reasons for this disruption include fear of contracting COVID-19, transportation challenges, and limited access to healthcare facilities due to lockdowns and restrictions.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous earlier studies that revealed unhealthy health-seeking behaviour lend support to this. According to a study conducted in Ethiopia, COVID-19 had a significant effect on patients' health-seeking behaviour, which was poor in 39% of patients [ 11 ]. Similar research conducted in Singapore during the COVID-19 outbreak indicated that 40% of chronic patients missed follow-up appointments [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Saah et al (2021) regarding treatment-seeking behavior during a pandemic found that during a pandemic, people tend to avoid disease risk factors and do things that can increase resilience. It was supported by Awel et al (2022) who found a decrease in visits for chronic disease patients due to fear of transmission of Covid-19. The results of a cohort study conducted by Chou et al (2021) found a decrease in health service visits.…”
Section: Introductionmentioning
confidence: 91%